Microextraction of Polycyclic Musks from Surface Water with Deep-Eutectic-Solvent-Coated Membrane Followed by Gas-Chromatography–Mass Spectrometry Analysis - Terlizzi, Fabiana; Fernandes, José O.; Gonzalez, Tamara; Petrarca, Mateus H.; dos S. Silva, Leandro; Lamarca, Rafaela S. [UNESP]; Gonzalez, Mario H. [UNESP]; Lapa, Rui; Cunha, Sara C. (MDPI, 2025)
Deep eutectic solvents (DESs), a novel class of eco-friendly solvents, are attracting considerable attention in extraction techniques. In this study, a hydrophobic DES, created by combining a quaternary ammonium salt and hexanoic acid, was coated onto a commercial cellulose membrane for polycyclic musks (cashmeran, celestolide, galaxolide, and tonalid) microextraction from surface waters followed by gas-chromatography–mass spectrometry (GC MS) analysis. A series of DESs were synthesized and characterized to identify suitable candidates for use as a coating on cellulose membranes. A factorial design approach was employed to investigate key factors, including DES volume, membrane type, dissolving solvent volume, DES incorporation time, and extraction duration, following a preliminary selection of the DES type, membrane, and dissolving solvent. Under optimized conditions, a cellulose acetate membrane impregnated with DES (TBAB:C6, 1:3 molar ratio) was used for 1 h to extract polycyclic musks from surface water; the extract was then dissolved in methanol prior to the GC-MS analysis. The DES-coated membrane demonstrated a linear detection range from 2.5 to 100 μg/L, with limits of detection (LODs) ranging from 0.06 to 0.15 µg/L, while the LOQ values varied from 0.2 to 0.5 µg/L. The validated method was successfully applied to real samples, allowing us to find the presence of galaxolide and tonalide.